Efeito da irrigação no desenvolvimento de porta-enxertos de seringueira (Hevea brasiliensis Muell. Arg) em dois substratos - Silva, Antonio Francisco da (1984)
This work was carried out in a greenhouse at the Federal University of Ceará - "Campus do Pici", Fortaleza-CE, to study the effect of six irrigation levels and two soil conditions in the development of rubber plants ( Hevea brasiliensis Muell. Arg). [...]